1994
DOI: 10.1016/s0248-4900(94)80013-8
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the 3‐D in vitro growth of human RT112bladder carcinoma cells using the alginate culture technique

Abstract: We studied the response to different in vitro culture conditions and the ability for polarization in three-dimensional (3-D) and two-dimensional (2-D) cell culture systems of the commonly used human bladder carcinoma cell line RT112. In the case of 2-D culture the cells were grown on glass or plastic coverslips, filter membranes, or bovine lens capsules. The alginate culture technique (ACT) was used to test the effects of 3-D cell culture on the polarization of the RT112 epithelial cells. Our studies show clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Chang human conjunctiva cells (ATCC CCL20.2) and RT112 human bladder carcinoma cells [16] were cultured as monolayers in DMEM medium supplemented with 10% fetal calf serum (FCS) at 37°C in 5% CO2. The human myelomonocytic cell line JOSK-M and myelocytic HL60 cells, obtained from the German Collection for Microorganisms, Braunschweig (DSM ACC30 and DSM ACC3), were grown as suspensions in RPMI 1640 (Gibco BRL, Paisley, UK) supplemented with 10% FCS (Boehringer Mannheim, Germany), 2 mM L-glutamine at 37°C, 5% C0 2 .…”
Section: Cells and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Chang human conjunctiva cells (ATCC CCL20.2) and RT112 human bladder carcinoma cells [16] were cultured as monolayers in DMEM medium supplemented with 10% fetal calf serum (FCS) at 37°C in 5% CO2. The human myelomonocytic cell line JOSK-M and myelocytic HL60 cells, obtained from the German Collection for Microorganisms, Braunschweig (DSM ACC30 and DSM ACC3), were grown as suspensions in RPMI 1640 (Gibco BRL, Paisley, UK) supplemented with 10% FCS (Boehringer Mannheim, Germany), 2 mM L-glutamine at 37°C, 5% C0 2 .…”
Section: Cells and Culturementioning
confidence: 99%
“…To test whether the ability of the IgAl protease to cleave phagosomal h-lamp-1 molecules could promote the intracellular accommodation and survival of N. gonorrhoeae, we investigated the survival of isogenic IgAl protease mutants in Chang conjunctiva epithelial cells, a well-characterised in vitro infection model [17,26], and RT112 bladder carcinoma cells [16]. For this purpose, we infected the cells with N. gonorrhoeae N303 (Opa 50 + , IgAl protease+) or with N876 (Opa 50 + , IgAl protease") at a bacteriaxell ratio of 30:1 for 6 h (Chang) or 12 h (RT112), respectively.…”
Section: Enhanced Survival Of Igal Protease-expressing Gonococci In Ementioning
confidence: 99%
“…Following the concept that a change in cell shape may initiate a corresponding change in cell function, the principal advantage of the 3-D technique appears to be the striking improvement in both cell morphology and polarity over that of conventional cultures. Recent investigations demonstrated that epithelial cell differentiation in vitro was greater when the cells were grown in 3-D cultures (Walling et al, 1991: Chevillard et al, 1993Boxberger and Meyer, 1994;Yamanari et al, 1994;Boxberger et al, 1995). Our in vitro system, which combines the advantages of cell lines and organ cultures, features the use of small vesicles of cultured epithelial ceils which appear to possess the original tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis was performed with the Genetics Computer Group and CLUSTALW programs and tools available at the website of the National Center for Biotechnology Information. Nucleotide and protein sequence homology (8). The T24 cell line was cultivated in McCoy's 5A medium supplemented with 2 mM glutamine, nonessential amino acids, and 10% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%